The Relationship Between Leadership Style, Job Satisfaction, and Work Environment with Nurse Performance in the Inpatient Ward - Dwi Rohyani (GLOBAL HEALTH SCIENCE GROUP, 2025)
Nurse performance refers to the execution of tasks, responsibilities, and authority in the best possible manner to achieve hospital goals in providing nursing services. In Indonesia, many hospitals have nurse performance levels below the ideal target of 75% of the available workforce. Objective to analyze the relationship between leadership style, job satisfaction, and work environment with nurse performance in the inpatient ward at Universitas Kristen Indonesia General Hospital. This quantitative study uses a cross-sectional design with a sample of 72 nurses, selected through total sampling. The research instruments include questionnaires on leadership style, job satisfaction, and work environment. Data were analyzed using the Chi-Square statistical test. 59.7% of nurses had moderate performance levels. 61.1% rated leadership style as moderate. 61.1% of nurses reported moderate job satisfaction. 68.1% assessed the work environment as moderate. Bivariate analysis showed a significant relationship between: Leadership style and nurse performance (p-value = 0.001); Job satisfaction and nurse performance (p-value = 0.001); Work environment and nurse performance (p-value = 0.001). There is a significant relationship between leadership style, job satisfaction, and work environment with nurse performance in the inpatient ward of Universitas Kristen Indonesia General Hospital.